Chemosensitization of solid tumors by inhibition of Bcl-xL expression using DNAzyme. - Yu, X.; Yang, L.; Cairns, M.; Dass, Crispin; Saravolac, E.; Li, X.; Sun, L. (Impact Journals LLC, 2014)
DNAzymes are a novel class of gene suppressors that selectively bind to an RNA substrate by Watson-Crick base pairing and cleave phosphodiester bonds. To explore the potential for therapeutic use of catalytic DNA molecules, active DNAzymes targeting the bcl-xL gene were generated through a multiplex in vitro selection. The DNAzyme-mediated down-regulation of the bcl-xL expression was demonstrated in various cancer cell lines by Western blots. Treatment of the cells with the active DNAzyme led to increases in percentage of apoptotic cells and cytochrome c release from mitochondria, a hall marker of apoptosis. When combined with chemotherapeutics such as Taxol, the DNAzyme significantly sensitised a panel of cancer cells to apoptosis as measured by cell survival assay. In Taxol-resistant cells, down-regulation of bcl-xL expression by the DNAzyme reversed the chemo-resistant phenotype of the cancer cells. In a xenograft mouse model, the DNAzyme was delivered into the tumors via an ALZET osmotic pump and shown to chemosensitize PC3 tumor when treating with Taxol. The results from the present study demonstrate that bcl-xL DNAzyme treatment facilitates apoptosis in solid tumors and suggest the potential use of bcl-xL DNAzyme in combination with chemotherapeutics for cancer therapy